PERKEMBANGAN ISLAM DI SUMATERA TIMUR (Strategi Komunikasi Politik Sultan di Asahan) - Mailin Mailin (Program Pascasarjana Universitas Islam Negeri Sumatera utara, 2016)
This research is a field related to the history of entry and his growing Islam in Asahan. This study aims to determine how the arrival of Islam in Asahan and how much influence the Sultan Asahan in Asahan First Islamize society. Asahan is one area Malay culture. Malay as a cultural group, has characteristics: speak Malay, Muslim, Malay customs and habitual. These values grow and expand and passed down from generation to generation. This research uses descriptive qualitative research method. The results showed that the process of entry and his growing Islam in Asahan originated from the government of Sultan Asahan I who ruled in the town of Asahan before the independence of the Republic of Indonesia. Political communication strategies Sultan saaat it is to a large extent the development of Islam in Asahan until now.